5(2x-6)=-3

Simple and best practice solution for 5(2x-6)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-6)=-3 equation:


Simplifying
5(2x + -6) = -3

Reorder the terms:
5(-6 + 2x) = -3
(-6 * 5 + 2x * 5) = -3
(-30 + 10x) = -3

Solving
-30 + 10x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + 10x = -3 + 30

Combine like terms: -30 + 30 = 0
0 + 10x = -3 + 30
10x = -3 + 30

Combine like terms: -3 + 30 = 27
10x = 27

Divide each side by '10'.
x = 2.7

Simplifying
x = 2.7

See similar equations:

| -10(2x-6)-6(10+3x)=8x+6x | | 0.4x=0.1(x-100)-70 | | (x-3)(x+3)+15=8x | | ((x^2)/6)-(2)=0 | | 7x-9+5x=6x-3 | | 7[1-(-8x-9)]=224x+259 | | t-1.23=4.56 | | 8x+7-6x=6 | | 8x-6=3x-4 | | (x^2/6)-2=0 | | -2(-5x-3)=-19x+5 | | 6m^2-12m-28=-10 | | 40x+x+110+x-30=180 | | 3X+4x-6=36 | | 3-2sqrtx=7 | | 20f+(-8f-15)=3(4f+5) | | 9-12x=-14 | | x^2+4x+8y-1=0 | | -20/-6 | | 4x+x=600 | | 6x-2=4x+8x-26 | | 4k^2-4k=6+2k^2 | | 2(-5x-3)=19x+5 | | 2b+6=9 | | X/5-2-9 | | 7(x-3)/45x/6 | | 0.5(14x+5)=9x+3 | | 3x+2y=37.50 | | 7+g=73 | | 4(y+3)+y=5Y+12 | | 2/5x-16 | | 4x-y^2=0 |

Equations solver categories